STUDY OF THE INFLUENCE OF DIFFERENT TYPES OF PHYSICAL EXERCISE ON QUALITY OF LIFE AND THE INDEX OF FEAR FALLS SENIORS. (Fiep Bulletin - online, 2015)
The present study aimed to evaluate which of the groups of physical exercise practiced by elderly offered better life quality. Considering which of these activities also accommodates smaller index of fear of falling, providing greater confidence to the elderly, since fall is one of the factors that interfere in their life quality. The quest for a better life quality in the old age require habits of healthy lives, what include the regular practice of physical activity, that assist the elderly during the aging process that their make suffer a lot of changes by several physical and physiological changes. The study had a comparative character, where 77 elderly were interviewed, with an average age between 60 and 80 years old, being divided into two groups, the “control group” who are the elderly not practitioners (inactive) of physical exercise and the “active group” who are practitioners of some sort of physical exercise. Into the active group, the elderly were subdivided according to the exercise practiced, group (A) dance practitioner, group (B) bodybuilder and group (C) water aerobics practitioner. The groups answered to three questionnaires: questionnaire of inactivity (IPAQ-6 version), fear of falls questionnaire (modification of Falls Eficacy Scale by Prevent of Falls Network Europe / Profane) and life quality questionnaire (WHOQOL-100), which were answered in the form of interview. The statistic used was descriptive using the program of Microsoft Office Excel 2007, noting the percentage, mean values and standard deviation and using t student to compare variables worked. It was found that the group that obtained the best results in the analysis of the life quality was the bodybuilders group, getting 3.8 points to items assessed in the questionnaire (L.Q physical, L.Q psychological and L.Q environment) of life quality, being under other groups only on an item (social relations) with 3.7 points, while the other groups have achieved 4 points. Regarding to the fear of falls, the dance (23.1) and bodybuilding (21.6) showed positive results, but the bodybuilding presented the best result. In the analysis of the percentage of falls and fear of falling, the bodybuilding presented the best result (62%) while the dance (80%) and water aerobics (94%) and the inactive group (90%) had higher results, especially the water aerobics. It was concluded that the group of exercise can provide better life quality for the elderly and less fear of falling was the bodybuilding.
Keywords: life quality; fear of falling; elderly and physical exercise.